Volume 4: Heat Transfer; Electric Power; Industrial and Cogeneration 1995
DOI: 10.1115/95-gt-001
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Film-Cooling Effectiveness on a Turbine Endwall Measured Using the Ammonia and Diazo Technique

Abstract: The distribution of adiabatic film-cooling effectiveness on the endwall of a large-scale low-speed linear turbine cascade has been measured using a new technique. This technique is based on an established surface-flow visualisation technique, and makes use of the reaction between ammonia gas and a diazo surface coating. A new method of calibration has been developed to relate the result of the reaction to surface concentration of coolant. Using the analogy that exists between heat and mass transfer the distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 0 publications
1
40
0
Order By: Relevance
“…Detailed endwall film cooling results have been conducted by Friedrichs et al [24][25][26] and Knost and Thole [27,28]. The results of the studies by Friedrichs et al indicated a strong influence of the secondary flows on the film cooling and an influence of the film-cooling on the secondary flows.…”
Section: Endwall Cooling Studiesmentioning
confidence: 91%
“…Detailed endwall film cooling results have been conducted by Friedrichs et al [24][25][26] and Knost and Thole [27,28]. The results of the studies by Friedrichs et al indicated a strong influence of the secondary flows on the film cooling and an influence of the film-cooling on the secondary flows.…”
Section: Endwall Cooling Studiesmentioning
confidence: 91%
“…Region 1-4 separated by red lines have been pointed out by Friedrich et al [11] as distinct regions requiring individual cooling hole placements. However, the division of these four regions only represents the influence of horseshoe vortex, passage vortex and secondary flow on endwall cooling design.…”
Section: Endwall Film Cooling Characteristicsmentioning
confidence: 96%
“…In the blade to blade plane, each row has a compound angle equal to the mean flow angle at mid span. This setting was the same used in the planar endwall investigation (Barigozzi et al, 2006), originally chosen in agreement with Friedrichs et al, 1996. Air at ambient temperature (or slightly heated with a density ratio DR = 0.95) was blown as cooling flow. The influence of density ratio on film cooling performance is well documented in the open literature (Hah et al, 2000).…”
Section: The Tunnel and The Test Modelsmentioning
confidence: 99%